Surfactin Like Broad Spectrum Antimicrobial Lipopeptide Co-produced With Sublancin From Bacillus subtilis Strain A52: Dual Reservoir of Bioactives - Sharma, Deepika; Singh, Shelley Sardul; Baindara, Piyush; Sharma, Shikha; Khatri, Neeraj; Grover, Vishakha; Patil, Prabhu B.; Korpole, Suresh (Frontiers in Microbiology, 2020)
An antimicrobial substance producing strain designated as A52 was isolated from a marine sediment sample and identified as Bacillus sp., based on 16S rRNA gene sequence analysis. The ANI and dDDH analysis of the genome sequence displayed high identity with two strains of B. subtilis sub sp. subtilis. Strain A52 yielded two antimicrobial peptides (AMPs) that differed in activity spectrum. MALDI mass spectrometry analysis of HPLC purified fractions revealed mass of peptides as 3881.6 Da and 1061.9 Da. The antiSMASH analysis of genome sequence unraveled presence of identical biosynthetic cluster involved in production of sublancin from B. subtilis sub sp. subtilis strain 168, which yielded peptide with identical mass. The low molecular weight peptide is found to be a cyclic lipopeptide containing C16 β-hydroxy fatty acid that resembled surfactin-like group of biosurfactants. However, it differed in fatty acid composition and antimicrobial spectrum in comparison to other surfactins produced by strains of B. subtilis. It exhibited broad spectrum antibacterial activity, inhibited growth of pathogenic strains of Candida and filamentous fungi. Further, it exhibited hemolytic activity, but did not show phytotoxic effect in seed germination experiment. The emulgel formulation of surfactin-like lipopeptide showed antimicrobial activity in vitro, and did not show any irritation effects in animal studies using BALB/c mice. Moreover, surfactin-like lipopeptide displayed synergistic activity with fluconazole against Candida, indicating its potential for external therapeutic applications.